Characterization of Cryopreserved Canine Amniotic Membrane - Nathawan Withavatpongtorn (MDPI AG, 2021)
Amniotic membrane is an effective corneal reconstruction material in veterinary surgery. Cryopreserved amniotic membrane is widely used in practice. Properties of cryopreserved canine amniotic membranes are currently not well studied. This study aimed to compare three properties between canine amniotic membranes cryopreserved for 7 days and 30 days, including tensile strength, transparency, and cell viability. After their respective cryopreservation time, stress–strain curves of the cryopreserved membranes’ tensile strength were assessed using a universal testing machine. Both groups produced J-shaped stress–strain curves with statistically comparable parameters, including maximum stress, strain, and Young’s modulus. The percentage of cell viability was observed by trypan blue staining under a light microscope. Membrane transparency was tested with a spectrophotometer. Transparency tests showed high levels of light transmission and low haze, with no statistical difference between groups. Cell viability was statistically lower in the 30-day cryopreserved group. Tensile strength and transparency of cryopreserved CAM were not significantly impeded for up to 30 days. For CAM to be used as an alternative corneal transplant material in veterinary and regenerative medicine, further research on cell biology, biomechanical properties of the membrane, and cell viability should be conducted.